Nanosystems in the Skin: from Undesirable Nanomaterial Exposure to Novel Nanoformulations - Nastiti, Christofori Maria Ratna Rini (Curtin University, 2019)
Nanomaterials are widely used in medical, pharmaceutical and industrial areas. The thesis investigated nanosystems in the skin. First, establishing through in vitro skin studies that nanomaterials accumulate on the skin surface and follicles with minimal potential for toxicity. Second, developing novel nanocarrier delivery systems to target the natural potent antioxidant resveratrol within the skin. Nanoemulsions hold great promise for targeted skin delivery skin for a range of cosmeceutical and dermatological purposes.